Specific growing features of variable section sapphire articles by Stepanov technique - Konevskiy, P.V.; Andreev, E.P.; Lytvynov, L.A. (Functional Materials, 2008)
Problems in growth of variable section corundum crystals by Stepanov technique have been considered. The structure perfection of the crystal profile variation zone has been studied as a function of the growing technology parameters. A procedure has been developed to provide variable section sapphire profiles of optical quality.